Thyrotoxicosis: An Updated Review for Physicians, Pharmacists, Anesthesiologists, and Healthcare Providers - Al MEHMADI , Fahad Mohammed; hakami , husssein abdu; Al-Otaibi, Sheaya Ali; quhal, Afnan muteb dahesh; ALFEHAID, ANAS FAHAD; Hagshah, Abdullah Saad; Mayuf, Khalid Mohammed Bin; Alghamdi , Salem Saud; Sufyani , shaqraa hsn; Almutairi, Amal Abdulali; ALMUTAIRI, JAMILA ABDULAALI; alotaibi, Meshal meshari; et al. (Journal of Ecohumanism, 2024)
Thyrotoxicosis is a clinical syndrome resulting from excessive thyroid hormone activity, primarily involving triiodothyronine (T3) and thyroxine (T4). It is distinct from hyperthyroidism, which specifically refers to overproduction of thyroid hormones by the thyroid gland. Thyrotoxicosis encompasses various conditions, including Graves' disease, thyroiditis, toxic nodules, and exogenous hormone intake. If untreated, it can lead to severe complications such as cardiovascular dysfunction, osteoporosis, and thyroid storm, a life-threatening emergency. The condition presents with diverse symptoms, including weight loss, heat intolerance, palpitations, and anxiety, necessitating a thorough diagnostic approach.This review aims to provide an updated overview of thyrotoxicosis, focusing on its etiology, pathophysiology, clinical presentation, diagnostic evaluation, and management strategies. It also highlights the importance of differentiating thyrotoxicosis from other conditions with similar presentations and discusses emerging therapies and ongoing research. Review also focusses on the main role of pharmacists and anesthesiologists in the management of thyrotoxicosis. The review synthesizes current literature on thyrotoxicosis, including its epidemiology, pathophysiology, and treatment modalities. It incorporates clinical guidelines, diagnostic criteria, and therapeutic approaches, supported by evidence from recent studies and trials. Special considerations for specific populations, such as pregnant women and children, are also discussed. Thyrotoxicosis is mostly caused by Graves' disease, toxic multinodular goiter, and thyroiditis. Diagnosis relies on suppressed TSH levels and elevated T3/T4 levels, with imaging studies aiding in identifying the underlying cause. Treatment options include beta-blockers for symptom relief, thionamide drugs, radioiodine therapy, and thyroidectomy. Emerging therapies, such as teprotumumab for Graves' orbitopathy, show promise. Early diagnosis and tailored treatment are crucial to prevent complications and improve outcomes.